Metagenomic Insights Into the Effects of Rare-Earth Elements Supplementation on Rumen Digestibility and Meat Quality of Beef Cattle - Xu, Lanjiao; Wen, Luhua; Ge, Yu; Wan, Gen; Qu, Mingren; Xue, Fuguang (Frontiers in Microbiology, 2020)
Rare-earth elements (REE), supplemented as feed additives, effectively improved feed conversion and production performances of monogastrics. However, very little information exists on how REE supplementation affects ruminants. In the present study, twenty-four 18-month-old Jinjiang bull cattle, with initial body weight (BW) of 374.75 ± 14.02 kg, were randomly allotted into four dietary treatments with a 15-day-long preliminary trial: a control treatment (basal diet), a 400 mg/kg REE treatment (basal diet supplemented with 400 mg REE/kg DMI), an 800 mg/kg REE treatment (basal diet supplemented with 800 mg REE/kg DMI), and a 1,200 mg/kg REE treatment (basal diet supplemented with 1,200 mg REE/kg DMI). Based on the results, the optimum supplementation scale was chosen for a 60-day-long follow-up feeding procedure. At the end of the feeding period, all bull cattle were slaughtered. Feed intake, average daily weight gain, carcass performances, meat quality, and rumen microbiota were measured. Results indicate a positive response in terms of growth performance and gastrointestinal digestibility to REE supplementation, and 400 mg/kg DMI treatment presented the most average daily feed intake (ADFI), the best average daily weight gain (ADG), and the least F/G. REE also significantly decreased the ruminal propionate content compared with control treatment. As to microbiota, despite no increases in bacterial community abundance, there was a proliferation of Bacteroidetes and Tenericutes and suppression of Actinobacteria under REE treatment. Furthermore, REE treatment significantly increased the meat protein content and decreased meat fat content. There was also an increase in the activities of the enzymes related to lipid syntheses. Fatty acid synthetase (FAS) and malate dehydrogenase (MDH) were significantly suppressed, while the activity of the lipolysis-related enzyme, lipoproteinesterase (LPL), was enhanced. In summary, REE supplementation provided an effective regulation on ruminal microbiota, facilitation of ruminal fiber digestibility, promotion of feed conversion, suppression of lipid deposition, and finally, improved the production and meat quality of beef cattle.